Democracy kills - Hawksley, Humphrey (London, 2009)
For many years Western governments have insisted that the only way to achieve long-term prosperity and political stability is through a combination of free-market economics and democratic government. Yet, all evidence now indicates that this argument is both flawed and can also be the direct cause of war, disease and poverty. From Pakistan to Zimbabwe, from the Palestinian territories to the former Yugoslavia, from Georgia to Haiti attempts to install democracy through elections have produced high levels of corruption and violence. Parliaments represent not broad constituencies but vested interests and, amid much fanfare, constitutions are written, but rarely upheld. Humphrey Hawksley has reported economic and political trends throughout the world for more than twenty years. In "Democracy Kills," he offers a vivid - and frequently devastating - analysis of our devotion to democracy. Taking the reader from Latin America, where he looks at collapse, then resurrection of the Argentine economy and China's growing influence in the region, to Africa, where he examines abusive child labour in the chocolate industry and to Asia he constantly asks why, if some nations can move on and get rich, do others founder and fight. And what - if anything - we can do about it.
Keywords: Democracy-India